If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4y + -7w + -6)(3y + 4) = 0 Reorder the terms: (-6 + -7w + 4y)(3y + 4) = 0 Reorder the terms: (-6 + -7w + 4y)(4 + 3y) = 0 Multiply (-6 + -7w + 4y) * (4 + 3y) (-6(4 + 3y) + -7w * (4 + 3y) + 4y * (4 + 3y)) = 0 ((4 * -6 + 3y * -6) + -7w * (4 + 3y) + 4y * (4 + 3y)) = 0 ((-24 + -18y) + -7w * (4 + 3y) + 4y * (4 + 3y)) = 0 (-24 + -18y + (4 * -7w + 3y * -7w) + 4y * (4 + 3y)) = 0 (-24 + -18y + (-28w + -21wy) + 4y * (4 + 3y)) = 0 (-24 + -18y + -28w + -21wy + (4 * 4y + 3y * 4y)) = 0 (-24 + -18y + -28w + -21wy + (16y + 12y2)) = 0 Reorder the terms: (-24 + -28w + -21wy + -18y + 16y + 12y2) = 0 Combine like terms: -18y + 16y = -2y (-24 + -28w + -21wy + -2y + 12y2) = 0 Solving -24 + -28w + -21wy + -2y + 12y2 = 0 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '24' to each side of the equation. -24 + -28w + -21wy + -2y + 24 + 12y2 = 0 + 24 Reorder the terms: -24 + 24 + -28w + -21wy + -2y + 12y2 = 0 + 24 Combine like terms: -24 + 24 = 0 0 + -28w + -21wy + -2y + 12y2 = 0 + 24 -28w + -21wy + -2y + 12y2 = 0 + 24 Combine like terms: 0 + 24 = 24 -28w + -21wy + -2y + 12y2 = 24 Add '2y' to each side of the equation. -28w + -21wy + -2y + 2y + 12y2 = 24 + 2y Combine like terms: -2y + 2y = 0 -28w + -21wy + 0 + 12y2 = 24 + 2y -28w + -21wy + 12y2 = 24 + 2y Add '-12y2' to each side of the equation. -28w + -21wy + 12y2 + -12y2 = 24 + 2y + -12y2 Combine like terms: 12y2 + -12y2 = 0 -28w + -21wy + 0 = 24 + 2y + -12y2 -28w + -21wy = 24 + 2y + -12y2 Reorder the terms: -24 + -28w + -21wy + -2y + 12y2 = 24 + 2y + -12y2 + -24 + -2y + 12y2 Reorder the terms: -24 + -28w + -21wy + -2y + 12y2 = 24 + -24 + 2y + -2y + -12y2 + 12y2 Combine like terms: 24 + -24 = 0 -24 + -28w + -21wy + -2y + 12y2 = 0 + 2y + -2y + -12y2 + 12y2 -24 + -28w + -21wy + -2y + 12y2 = 2y + -2y + -12y2 + 12y2 Combine like terms: 2y + -2y = 0 -24 + -28w + -21wy + -2y + 12y2 = 0 + -12y2 + 12y2 -24 + -28w + -21wy + -2y + 12y2 = -12y2 + 12y2 Combine like terms: -12y2 + 12y2 = 0 -24 + -28w + -21wy + -2y + 12y2 = 0 The solution to this equation could not be determined.
| Ln(x-2)=2-ln(x-4) | | 16x-24=2x-10 | | -x+156=268 | | (9+w)(5w-8)=0 | | 7e+2=3e+8 | | 21+2x=171 | | 2(x-2)=3x-2 | | 9b+b+8b=(-23) | | 212-v=130 | | x=8037.42-x-.01 | | 2(x-1)=5(x-7) | | x=.014-8037.42 | | (2y+5)(3-y)=0 | | 17-5*3+4= | | 0=(-16t^2)+(48t)+(160) | | 10x-6=10+2x | | (x+2)2=64 | | 12+8y=18 | | 15v^2+11v-12= | | 6x+14y=26 | | -1/2x-2/3=1/7 | | 3(2x+1)=(-39) | | 12x-11=10x-1 | | B^3/4=16 | | f=f(R) | | 2x+12=31-3(x) | | 6=u/2 | | 1-x=.9114 | | 2x-12=4x+8 | | x^2-3ay+2y^2=0 | | 41x+2-38x=26 | | 11x-5=7x |